PDE10A and PDE10A-dependent cAMP catabolism are dysregulated oppositely in striatum and nucleus accumbens after lesion of midbrain dopamine neurons in rat: A key step in parkinsonism physiopathology - M. Giorgi; G. Melchiorri; V. Nuccetelli; V. D'Angelo; A. Martorana; R. Sorge; V. Castelli; G. Bernardi; G. Sancesario (Neurobiology of Disease, 2011)
Loss of dopamine neurons in experimental parkinsonism results in altered cyclic nucleotide cAMP and cGMP levels throughout the basal ganglia. Our objective was to examine whether expression of phosphodiesterase 10A (PDE10A), an isozyme presenting a unique distribution in basal ganglia, is altered after unilateral injection of 6-hydroxydopamine in the medial forebrain bundle, eliminating all midbrain dopaminergic neurons, such that cyclic nucleotide catabolism and steady state could be affected. Our study demonstrates that PDE10A mRNA levels were decreased in striatal neurons 10 weeks after 6-hydroxydopamine midbrain lesion. Such changes occurred in the striatum ipsilateral to lesion and were paralleled by decreased PDE10A protein levels and activity in striatal neurons and in striato-pallidal and striato-nigral projections. However, PDE10A protein and activity were increased while PDE10A mRNA was unchanged in the nucleus accumbens ipsilateral to the 6-hydroxydopamine midbrain lesion. Accordingly, cAMP levels were down-regulated in the nucleus accumbens, and up-regulated in the striatum ipsilateral to the lesion, but they were not significantly changed in substantia nigra and globus pallidus. Unlike cAMP, cGMP levels were decreased in all dopamine-deafferented regions. The opposite variations of cAMP steady state in striatum and nucleus accumbens are concordant and likely dependent, at least in part, on the down-regulation of PDE10A expression and activity in the former and its up-regulation in the latter. On the other hand, the down-regulation of cGMP steady state in the striato-nigral and striato-pallidal complex is not consistent with and is likely independent from the concomitant down-regulation of PDE10A. Therefore, dopamine loss inversely regulates PDE10A gene expression in the striatum and PDE10A post-transcription in the nucleus accumbens, therein differentially modulating PDE10A-dependent cAMP catabolism.